Expanding Conversations of Race and the Nation: A Closer Look at The Fish Eyes Trilogy by Anita Majumdar - Bains, Alysha (Theatre Research in Canada / Recherches théâtrales au Canada, 2020)
“Coming of age” narratives in multicultural Canada often construct an ideal that is not attainable for many Black, Indigenous, and young people of colour growing up in the country. Often times, experiences of racialized young people are dismissed and cast aside. This article explores how Anita Majumdar’s The Fish Eyes Trilogy acts as a tactic of resistance to this reality. Tactics of resistance as argued by feminist media scholar Yasmin Jiwani help us to imagine different ways of seeing the world that is often presented to us. As a tactic of resistance, The Fish Eyes Trilogy uses parody, disrupts homogeneity of South Asian experiences in Canada, and reverses the dominant white gaze. This three-part play offers a curious site for reimagining how we can expand and critique discussions of race with young people in Canadian theatre.